Hannah Arendt e a abrangência do conceito de Banalidade do Mal - Kelson, Ruth (2011)
This dissertation intends to enlarge the scope of the concept Banality of Evil, a term coined by Hannah Arendt to qualify an Evil that had not yet been detected as a particular form and that she had observed in the Nazi Adolph Eichmann during his trial in Jerusalem in 1962. She called it an Evil without roots, which is like a fungus in the surface. She found it in a nonperson, in someone that doesn t think , that doesn t perform the dialogue me-with-myself and acts in heteronomy, under an external command to which it obeys without assuming personal responsibility for its moral consequences. This concept helps to elucidate the way totalitarianisms of the modern era acts and the attitude of those that only follow orders , without considering the monstrosities that they can embed. The first condition for this new form of Evil was man s preceding transformation in a pure animal laborans, dedicated nearly exclusively to his survival as a species. Transformed in a thing, as a mean and not an end in itself, man acquired the condition of superficiality from which it could derive the logic of extermination. The second condition was the destruction of the sacredness of man in modern times. With the death of God, he was transformed into a simple thing, able to be molded, used and discarded. The third condition is the predominance of the process in the world today which has an autonomous dynamics and is independent of man and his decisions. Zigmunt Baumann added to Hannah Arendt s vision a new comprehension of the mechanisms and motives that can slip into this form of Evil: the fight against the indeterminate, the chaotic and the ambivalence, trying to create a controlled and less threatening world. But, in the fight against ambivalence, an even greater chaos is created around this orders that are built. In this world on which one wants to impose the order of a deterministic law or project, the bureaucrat is the main agent of this form of Evil. The question of the Banality of Evil raises the question of what are the means at our disposal to oppose it